Application of combined Reliability Centered Maintenance and Risk Based Inspection Method to Improve the Effectiveness of Maintenance Management of Compressor ZR 5 Intercooler - Prabata, Sandika; Wiyana, Aldo Fantinus (The Indonesian Journal of Business Administration, 2012)
Compressor play the prominent role of the compressed air system. If The compressor find the trouble itself, then air supply to production line will be terminated. One of the big problem of Compressor ZR 5Â  take place on intercooler.Intercooler is the compressor component which function to cool compressed air inside the compressor so that the compressorÂ  will not be overheated. If overheated happens,then the alarm on compressor display will show â€œHigh Air Temperature on LP Element Outletâ€.Consequently, the compressor will shut down automatically & must be replaced by other standby compressor.Even intercooler routine maintenance is already performed periodically refer to maintenance manual itself, ( running hour/time based), howeverÂ  this alarm indication frequentlyÂ  shown pior to entering next period of maintenance schedule.PM Analysis (field observation) & root cause Analysis implementation lead to the cause ofÂ  the alarm indication. They consist of: low flow rate of cooling water that caused byÂ  stuck strainer (filter) on the pipe line, imperfect contact between cooling waterÂ  and compressed air due to poor quality of cooling water, Delay on Detection problemÂ  and lack of skill to analyse alarm trouble data.The proposed countermeasure will be provided as follows : relocate strainer position so that easy maintenance could be executed, to modify new pipe line with new cooling water source (from treated reuse water to public water) with more complianceÂ  to water requirement, Introduction of stochastic methodÂ  (replacement & inspection model) to predict effective inspection, cleaning and replacement of intercooler, maintenance management training provision includingÂ  diagnostic problem andÂ  water cooling system maintenance of compressor. However, the countermeasure mentioned above only to encounter abnormality found at the time of observation to compressor cooling water system. By applying combined RCM & RBI method, other potential cause that might result in the same problem could be identified, so that the problem will not be recurrence. The countermeasure (corrective action) & preventive action need should be analised for the pros & cons (cost & benefit analysis) so that this activity will provide important information for management. Based on the CBA, this activity will provide payback period for 3 months. The activity will involve external party (contractor) to perform corrective action & internal party (operator member) to conduct maintenance task as already scheduled. Â  Keywords: Intercooler,,PM analysis, Root Cause Analysis, RCM & RBI, Stochastic Â Method